Agricultural Adaptation Strategies to Weather Fluctuations for Improved Agribusiness Sustainability in West Java - Zulfikri, Agung; Ningsih, Elik Murni Ningtias; Harsono, Iwan; Susanto, Himawan (Westscience Press, 2024)
This research investigates agricultural adaptation strategies to weather fluctuations for enhancing agribusiness sustainability in West Java, Indonesia. Employing a qualitative research methodology, the study delves into the challenges posed by climate variability and the responses of farmers and agribusiness stakeholders to mitigate these challenges. Through interviews, focus group discussions, and participant observation, the research identifies key weather-related challenges, including erratic rainfall patterns, temperature extremes, natural disasters, and pest outbreaks. Furthermore, the study explores adaptation strategies such as crop diversification, water management, soil conservation, adoption of climate-resilient crop varieties, and agroforestry. The findings contribute to understanding the complexities of agricultural adaptation and offer insights for policymakers, practitioners, and stakeholders to promote sustainable agribusiness development in West Java and similar regions facing climate-related challenges.